2015
DOI: 10.1049/iet-nbt.2015.0001
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of silver nanoparticles for selective toxicity towards cancer cells

Abstract: Therapeutic applications of nanoparticles (NPs) are rapidly increasing for their utility in medicine, especially cancer therapy. The present study investigated the green synthesis of silver NPs (Ag NPs) of 10 nm size using Sargassum vulgare and its preferential ability to kill cancerous human myeloblastic leukemic cells HL60 and cervical cancer cells HeLa as compared with normal peripheral blood mononuclear cells. DNA fragmentation study and annexin V marker fluorescence-activated cell sorting (FACS) analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…In line with our results, several studies have shown that ZnO NPs or other types of NPs induce DNA damage in a variety of cell types. [50][51][52][53][54][55][56][57][58][59][60] In vivo exposure to ZnO NPs alters the structure of seminiferous tubules and spermatozoa morphologies…”
Section: Zno Nps Induce Nuclear Dna Leakage and Breakagementioning
confidence: 99%
“…In line with our results, several studies have shown that ZnO NPs or other types of NPs induce DNA damage in a variety of cell types. [50][51][52][53][54][55][56][57][58][59][60] In vivo exposure to ZnO NPs alters the structure of seminiferous tubules and spermatozoa morphologies…”
Section: Zno Nps Induce Nuclear Dna Leakage and Breakagementioning
confidence: 99%
“…These results were similar to the effects of silver nanoparticles on the cancer cells of the HL60 myeloblastic leukemia, Hella's cancer cells and healthy peripheral blood cells. With the influences of silver nanoparticles on cells and peroxidation of fats, free radicals of ROS are formed that damage DNA and induce apoptosis (35). In addition, in the present study, apoptosis was evaluated in HPB-ALL cell line and lymphocytes by silver nanoparticles and Flow Cytometry that showed the values of 22.75% and 6.04%, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Microscopy studies showed the endocytosis of silver nanoparticles into the nucleus of the cell which caused DNA damaged and ultimately led to apoptosis. These findings show potential for silver nanoparticles to be used in cancer therapy [151].…”
Section: Use Of Silver Nanoparticles For Drug Delivery and As Cancer mentioning
confidence: 70%
“…Because of silver nanoparticles extraordinary antimicrobial activity it is mainly used in the medical industry for textiles, wound dressings and device coatings. However, the use of silver nanoparticles in biomedical applications such as biosensors [133][134][135] photothermal therapy and drug delivery [144][145][146][147][148][149][150][151][152][153][154] is increasing and will be discussed in Section 4.…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%